Variasi Bahasa Arab Dari Segi Penutur Dalam Film Arab Imam Ahmad Bin Hanbal Seri Pertama - Hidayat, Tatang; Mufarokah, Siti; Huda, Syirojul (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2023)
Language variation is a very important subject to study, because the role of language is very important in social life. This research aims to find out the historical overview of the Imam Ahmad bin Hambal Arabic film series and to find out the Arabic language variations in terms of speakers contained in the dialog of the Imam Ahmad bin Hambal Arabic film. This research uses qualitative approach and descriptive method. The data retrieval technique used the method of simak bebas libat cakap (SBLC). The results of this study are; first, the Imam Ahmad bin Hanbal series is a major historical television series. It is a series produced by Qatar Media Foundation in collaboration with its Qatari partner Al-Buraq for media production. A large group of representatives from 7 Arab countries participated in it with more than 70 actors and actresses. It took two years to prepare the series, starting from 2015 until the series aired in Ramadan (2018) and the series was executed and filmed in Lebanon and Turkey. Second, language variation in terms of speakers in the dialog of Imam Ahmad bin Hanbal's Arabic film is sociolect, vulgarity, and cant. Sociolect in this movie includes sociolect in terms of education and gender.